Transitioning Between Prostanoid Therapies in Pulmonary Arterial Hypertension - Pan, Irene Z.; Carey, Jessica R.; Jacobs, Joshua A.; Dechand, John; Sessions, Joshua J.; Sorensen, Teshia; Penn, Brittany A.; Mayeux, Jennalyn D.; Hatton, Nathan D.; Ryan, John J. (Frontiers in Medicine, 2020)
Background: New oral prostacyclin therapies and prostacyclin agonists have become available for the treatment of pulmonary arterial hypertension (PAH). However, methods for transitioning between oral, inhaled, and parenteral formulations are not well-established, except in the form of case reports and case series. Collectively, these emphasize the lack of a standardized process and approach in transitioning patients between PAH prostanoid therapies. In this case series, we report our experience at an accredited Pulmonary Hypertension center in transitioning between various oral, inhaled, and parenteral prostanoids to offer additional guidance on safe transitions in therapy. Methods: All cases of prostanoid transitions at an accredited Pulmonary Hypertension center from March 2018 to September 2019 were included in this report. The transition approach for each case was developed through a review of the literature, extrapolation of available pharmacokinetic data, and collaboration between pharmacists and clinicians. Results: This case series describes the transition of 3 patients from selexipag to parenteral treprostinil; 1 patient transitioning from parenteral treprostinil to selexipag; 1 patient transitioning from oral treprostinil to parenteral treprostinil; and 1 patient transitioning from inhaled treprostinil to selexipag. Four of the 6 patients presented here were transitioned to an alternate prostanoid on account of clinical worsening, while the remaining 2 patients transitioned due to intolerance of parenteral therapy and poor medication adherence. This case series includes patients with various etiologies of PAH including idiopathic PAH, methamphetamine-associated PAH, and scleroderma-associated PAH. All patients successfully completed each transition without serious adverse events. Conclusions: With the increasing utilization and availability of prostanoids, there is a critical need for a standardized approach in transitioning safely between different formulations without compromising treatment efficacy. In this case series, we present our clinical experiences, guided by available pharmacokinetic data, in transitioning between various prostanoid formulations.